Parasitic infections during pregnancy need not affect infant antibody responses to early vaccination against Streptococcus pneumoniae, diphtheria, or Haemophilus influenzae type B. - Noah D McKittrick; Indu J Malhotra; David M Vu; Derek B Boothroyd; Justin Lee; Amy R Krystosik; Francis M Mutuku; Charles H King; A Desirée LaBeaud (Public Library of Science (PLoS), 2019)
BACKGROUND:Globally, vaccine-preventable diseases remain a significant cause of early childhood mortality despite concerted efforts to improve vaccine coverage. One reason for impaired protection may be the influence of prenatal exposure to parasitic antigens on the developing immune system. Prior research had shown a decrease in infant vaccine response after in utero parasite exposure among a maternal cohort without aggressive preventive treatment. This study investigated the effect of maternal parasitic infections on infant vaccination in a more recent setting of active anti-parasitic therapy. METHODOLOGY/PRINCIPAL FINDINGS:From 2013-2015, 576 Kenyan women were tested in pregnancy for malaria, soil-transmitted helminths, filaria, and S. haematobium, with both acute and prophylactic antiparasitic therapies given. After birth, 567 infants received 10-valent S. pneumoniae conjugate vaccine and pentavalent vaccine for hepatitis B, pertussis, tetanus, H. influenzae type B (Hib) and C. diphtheriae toxoid (Dp-t) at 6, 10, and 14 weeks. Infant serum samples from birth, 10 and 14 weeks, and every six months until age three years, were analyzed using a multiplex bead assay to quantify IgG for Hib, Dp-t, and the ten pneumococcal serotypes. Antenatal parasitic prevalence was high; 461 women (80%) had at least one and 252 (43.6%) had two or more infections during their pregnancy, with the most common being malaria (44.6%), S. haematobium (43.9%), and hookworm (29.2%). Mixed models comparing influence of infection on antibody concentration revealed no effect of prenatal infection status for most vaccine outcomes. Prevalences of protective antibody concentrations after vaccination were similar among the prenatal exposure groups. CONCLUSIONS/SIGNIFICANCE:These findings are in contrast with results from our prior cohort study performed when preventive anti-parasite treatment was less frequently given. The results suggest that the treatment of maternal infections in pregnancy may be able to moderate the previously observed effect of antenatal maternal infections on infant vaccine responses.